6. Solve for \( d \) \( 3(1-d)-8=d+7-4 d \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Mind Expander
To solve for \( d \), let's start by distributing on the left side of the equation: \( 3(1 - d) - 8 = d + 7 - 4d \) This simplifies to: \( 3 - 3d - 8 = d + 7 - 4d \) Combine like terms on both sides: Left side: \( 3 - 8 = -5 \), so we have: \( -3d - 5 = d + 7 - 4d \) Now, simplify the right side: Combine \( d \) and \( -4d \): \( d - 4d = -3d \) So now the equation is: \( -3d - 5 = -3d + 7 \) Next, add \( 3d \) to both sides to eliminate \( d \): \( -5 = 7 \) Oops! We found that this results in a contradiction. Therefore, there is no solution for \( d \) because the equation simplifies to an impossible statement.